Testing IT : an off-the-shelf software testing process - Watkins, John (John Edward) (Cambridge University Press, 2011)
"Testing IT provides a complete, off-the-shelf software testing process framework for any testing practitioner who is looking to research, implement, roll out, adopt, and maintain a software testing process. It covers all aspects of testing for software developed or modified in-house, modified or extended legacy systems, and software developed by a third party. Software professionals can customize the framework to match the testing requirements of any organization, and six real-world testing case studies are provided to show how other organizations have done this. Packed with a series of real-world case studies, the book also provides a comprehensive set of downloadable testing document templates, proformas, and checklists to support the process of customizing. This new edition demonstrates the role and use of agile testing best practices and includes a specific agile case study"--Provided by publisher